PENGARUH NAUNGAN TERHADAP HASIL KACANG TANAH (Arachis hypogaea L.) DI DESA CAMPLONG II KECAMATAN FATULEU - Vinni Y.K. Uji; Nur Aini Bunyani, Abdonia W. Finmeta (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research was carried out in Camplong II Village, Fatuleu District, from 6 February to 6 May 2024. The research method used in this research was the Randomized Group Design (RAK) method which consisted of 3 levels of treatment, namely: treatment without shade, treatment with shade 60 % and 80% shade treatment which was repeated 3 times and 5 plants were taken as samples for each repetition, so there were 45 plants as observation units. The results of this research show that the no shade treatment, 60% shade treatment and 80% shade treatment showed the number of seeds and pod weight in peanut plants. The conclusion from this research is that treatment without shade is the treatment that provides maximum results for all parameters.